Effect of Crown Dimensions on Stress Distribution in Implant Abutment Screw: A 3D Finite Element Analysis - F Zolfagharloo; N Nasr; O Tavakkol; M Momayezinejad (Islamic Azad University, 2023)
Background and Aim:   This study assessed the effect of crown dimensions on stress distribution in the abutment screw upon loading using three-dimensional (3D) finite element analysis (FEA). Materials and Methods: Eighteen finite element models were designed using Mimics, 3D-Matic, Catia, and ANSYS software programs. Implant models were designed with 8.5-, 10- and 11.5-mm fixture heights, three different vertical cantilever heights of 8, 10, and 12 mm, and two horizontal cantilever lengths of 7 and 14 mm for the mandibular first and second molars. The interaction effect of of 120 N and 20 N loads on the implant and implant crown at the site of first molar, and the interaction effect of 150 N and 25 N loads on the cantilever at the site of second molar were analyzed. Results: By an increase in horizontal cantilever length, stress in the abutment screw, abutment, and fixture increased in all models. Stress decreased in the abutment screw and increased in the abutment and fixture by an increase in vertical cantilever. Minimum screw stress was recorded in implants with 8.5 mm fixture height, 7 mm horizontal cantilever, and 12 mm vertical cantilever. Maximum screw stress was noted in implants with 11.5 mm fixture height, 14 mm horizontal cantilever, and 8 mm vertical cantilever. Conclusion: According to FEA, increasing the horizontal and vertical cantilever length may result in an increased risk of screw loosening and fatigue fracture due to increased stress values in the screw or in other components (abutment and fixture), respectively.